Improving Energy Efficiency with Heat Exchanger and Optimizing Operating Conditions for Sorbitol Production from Dextrose - Vernando, Dio Fani; Rodifa, Muhammad; Muhammad, Rizdian Arsyal; Simanungkalit, Raysa Yuliana Br (UPT Laboratorium Terpadu, Universitas Diponegoro, 2024)
Sorbitol is a sugar alcohol which has a molecular formula of C6H14O6. The production of sorbitol by the hydrogenation process is carried out at high pressure so that a large amount of energy is required. The use of considerable energy in the production process supports the need for innovation for energy efficiency in the production of sorbitol from dextrose, which is expected to help increase sorbitol production so that it can meet market needs. The innovation carried out here is to change the operating conditions with the help of Ru/ASMA@AC catalyst so that the temperature required during the reaction is low. In addition, modifying the use of heat exchanger units so that the heat generated during operation is reused. These innovations were simulated using Aspen HYSYS software. The results of the simulation proved to be able to improve energy efficiency by reducing the performance of compressors and coolers used during production and saving considerable energy. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).